Ideologijska strukturiranost socijalno-ekonomskih orijentacija - Šram, Zlatko (Array, 2008)
In this research, we tried to answer the following questions: fi rstly, is there within the space of socio-economic orientations an internally coherent model of neoliberal ideology or possibly a mixed ideological pattern, and secondly, whether the participants of various socio-economic statuses differ among themselves with regard to the degree of internalisation of specifi c latent economic-social dimensions. The research was conducted on a sample of fi rst year students at University of Zagreb (N=223). Factor analysis of economicsocial orientations yielded four factors labelled Free-market orientation, Egalitarianism, Entrepreneurial orientation, and State Interventionism. Therefore, we did not determine the existence of a coherent model of neoliberalism within which the values of liberal-individualistic and egalitarian-etatistic orientations were necessary mutually excluded. The results of canonical discriminant analysis have shown that the mixture of egalitarian-etatism and one component of liberalism are more expressed by the participants of lower passive socio-economic status. Factor analysis of socio-economic latent dimensions yielded two superfactors labelled Ideology of social liberalism, and Ideology of state interventionism. The results of canonical discriminant analysis have shown that the participants of lower passive socio-economic status express a mixed ideology of social liberalism and state interventionism more. In other words, only on the third level of canonical factors is it evident that an extremely confl icting ideological pattern is present in groups of lower socio-economic status. The research implicitly indicates the possibility that without an integral state social policy, and even more in the private sphere, various forms of political radicalisation in a transitional society might emerge